Hubungan Tingkat Pendidikan dan Lama Kerja dengan Waktu Tanggap Perawat di Instalasi Gawat Darurat RSUD Dr. Adjidarmo Rangkasbitung - Siti Rochani (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Nurse respond time is a significant matter by the emergency nurses in treating patients with accute injury or patients with life threatening illness. An inaprropriate respond time by the emergency nurse can lead patients to disability even to bodily damage that threatening life as well. Nurse respond time in treating patients in emergency instalation could be vary from one nurse to the other. This study led to know correlation between education level and time of service of emergency nurses to the nurses respond time in treating emergency patients in emergency instalation room of RSUD Dr. Adjidarmo, Rangkasbitung. This quantitative study is a cross-sectional research method and took place in emergency instalation of RSUD Dr. Adjidarmo, Rangkasbitung during the month of June 2019. Research population and sample is all of the care giver nurse in emergency instalation of RSUD Dr. Adjidarmo, Rangkasbitung as much 30 nurses. The sampling is a total sampling with questionery and observation as measurement tools while data analysis managed in univariate and bivariate. The results show that respondends age avarage is 34 years old with 18 respondends (60%) are female and in level of education, respondends in Diploma are 18 (60%). The results of bivariate test show that p value 0,021 (<0,05) in level of education to the respond time and p value 0,049 (<0,05) in years of service to the respond time. There are significant correlation between level of education and years of service to the nurse time respond.